PREVENTIVE ACTIVITY OF TEACHER AS A MEANS PREVENTION OF ASOCIAL BEHAVIOR JUNIOR SCHOOLCHILDREN - L.Yu. Puzanova (Academy of Cognitive and Natural Sciences, 2022)
The article is dedicated pecularietes of pedagogical support and priventive activity to avoid unsocial tanager's behavior.